2014
DOI: 10.1002/pon.3539
|View full text |Cite
|
Sign up to set email alerts
|

Selective impairment of attention networks in breast cancer patients receiving chemotherapy treatment

Abstract: These results suggest that the three attention networks were selectively impaired following chemotherapy treatment, which affected different brain areas in the breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
21
1
Order By: Relevance
“…The intact orienting attention function found in HIV-infected patients is not unique. Using ANT, we have also found that an intact orienting attentional ability in patients with depression [38], untreated hyperthyroidism [39], and the breast cancer patients receiving chemotherapy treatment [40]. Previous studies have documented that cholinergic systems arising in the basal forebrain appear to play a critical role in orienting attention network [18, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…The intact orienting attention function found in HIV-infected patients is not unique. Using ANT, we have also found that an intact orienting attentional ability in patients with depression [38], untreated hyperthyroidism [39], and the breast cancer patients receiving chemotherapy treatment [40]. Previous studies have documented that cholinergic systems arising in the basal forebrain appear to play a critical role in orienting attention network [18, 41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, Posner and Fan designed a simple computer-based paradigm-Attention Network Test (ANT; Fan et al, 2002) to measure the three network efficiencies of attention. Some studies that have applied ANT to patients with focal frontal and parietal lesions (Hu et al, 2013) and breast cancer (Chen et al, 2014) have confirmed that ANT is reliable.…”
Section: Introductionmentioning
confidence: 94%
“…Cerebral small vessel disease (CSVD) refers to the clinical, cognitive, imaging, and pathological manifestations of cerebrovascular syndrome caused by small vessel arteries, arterioles, capillary, and venule change (Chen et al, 2019). The major imaging features of CSVD mainly include white matter hyperintensities (WMHs), enlarged perivascular space (EPVS), cerebral microbleeds (CMBs), and lacunar infarcts (LI;French et al, 2014). The clinical manifestations of CSVD include a wide range of symptoms, which are as follows: typical stroke symptoms, varying degrees of cognitive impairment from mild impairment to dementia (Meissner, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research suggests the effects of CT on specific domains of executive functioning. These findings suggest that CT-treated patients are vulnerable to cognitive control and monitoring (Chen et al, 2014;Yao, Bernstein, & Rich, 2017). Deficits in executive functioning may not have Fig.…”
mentioning
confidence: 91%